Penerapan terapi kompres aloevera untuk menurunkan suhu tubuh pada pasien hipertermi - Mahda Afsani; Rika Yulendasari; Eka Yudha Chrisanto (THE JOURNAL OF Mother and Child Health Concerns, 2023)
Background: According to WHO in 2018 there were 65 million cases of fever in children with different types of disease and 62% of cases of illness accompanied by fever symptoms, with a presentation rate of 33% and most cases were in Southeast Asia as well as South Asia. Purpose: To make a report on family nursing care by applying aloevera compress therapy to reduce body temperature in hyper thermic patients. Method: This writing uses the case study method with the Family Nursing Care approach with 2 respondents. The instruments used are SOPs for applying aloevera compress therapy to reduce body temperature in hyper thermic patients, observation sheets, and body temperature measuring devices. The study was conducted from 8 May to 10 May 2023 with the method of applying aloevera compress therapy to lower body temperature in hyper thermic patients. Results: body temperature before the intervention was 38.5º C, it became 37.5º C. Conclusion: The results of evaluating the application of aloevera compresses to patient An. F and An. H with fever within 3 days got the results: Hyperthermia associated with the disease process is resolved.   Keywords: Hyperthermia, Aloevera Compress Therapy; Lowering Body Temperature   Pendahuluan: Menurut WHO tahun 2018 terdapat 65 juta kejadian kasus demam pada anak dengan jenis penyakit yang berbeda serta 62% jumlah kasus penyakit yang disertai gejala demam, dengan tingkat presentasi kematian 33% dan kasus terbanyak terdapat di Asia Tenggara juga Asia Selatan. Tujuan: Untuk membuat laporan asuhan keperawatan keluarga dengan penerapan terapi kompres aloevera untuk menurunkan suhu tubuh pada pasien hipertermi. Metode: Penulisan ini menggunakan metode studi kasus dengan pendekatan Asuhan Keperawatan Keluarga dengan 2 responden. Instrumen yang digunakan yakni SOP penerapan terapi kompres aloevera untuk menurunkan suhu tubuh pada pasien hipertermi, lembar observasi , dan alat pengukur suhu tubuh.. Penelitian dilakukan dari 8 mei hingga 10 mei 2023 dengan metode penerapan penerapan terapi kompres aloevera untuk menurunkan suhu tubuh pada pasien hipertermi. Hasil: suhu tubuh sebelum diberkan intervensi 38,5 o C, menjadi 37,5o C. Simpulan: Hasil evaluasi penerapan kompres aloevera pada pasien An. F dan An. H dengan demam dalam kurun waktu 3 hari mendapat hasil: Hipertermi berhubungan dengan proses penyakit teratasi.